2016
DOI: 10.1590/0103-6440201600329
|View full text |Cite
|
Sign up to set email alerts
|

Penetration Capacity, Color Alteration and Biological Response of Two In-office Bleaching Protocols

Abstract: Hydrogen peroxide (H2O2) penetrates into the dental hard tissues causing color alteration but also alterations in pulpal tissues. Hard-tissue penetration, color alteration and the pulp response alterations were evaluated for two in-office bleaching protocols with H2O2. For trans-enamel/dentin penetration and color alteration, discs of bovine teeth were attached to an artificial pulp chamber and bleached according to the groups: BLU (20% H2O2 - 1x50 min, Whiteness HP Blue); MAX (35% H2O2 - 3x15 min, Whiteness H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
55
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 24 publications
3
55
0
1
Order By: Relevance
“…Studies have reported diffusion of H 2 O 2 into enamel and dentine (Cintra et al . ), reaching the dentine–pulp complex and reacting with pulp cells (Costa et al . , Cintra et al .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported diffusion of H 2 O 2 into enamel and dentine (Cintra et al . ), reaching the dentine–pulp complex and reacting with pulp cells (Costa et al . , Cintra et al .…”
Section: Introductionmentioning
confidence: 99%
“…, Cintra et al . ,b) and pulp necrosis (Cintra et al . ) caused by H 2 O 2 gels during dental bleaching procedures.…”
Section: Introductionmentioning
confidence: 99%
“…The low molecular weight of hydrogen peroxide (HP) promotes not only tooth bleaching but also the release of inflammatory mediators into the pulp, which may damage pulp cells and cause reversible pulpitis . A previous study of rat molars has shown that H 2 O 2 causes necrosis in the occlusal third of coronary pulp after one bleaching session . A similar outcome was found in a study of human teeth .…”
Section: Introductionmentioning
confidence: 70%